The Two Way Symmetrical Model in Establishing Take and Give Relations with Community - Iin Masruroh (Yayasan Avicenna, 2023)
Although the two-way symmetrical communication model has been widely discussed in public relations studies, limited research has examined its implementation in Islamic educational institutions, particularly in strengthening reciprocal relationships between madrasahs and local communities. This study aims to investigate how MA Subulus Salam implements the two-way symmetrical communication model to establish mutually beneficial relationships with the surrounding community. A qualitative descriptive approach was employed through interviews with key stakeholders, including education administrators, Islamic boarding school administrators, regional boarding school leaders, and school management, complemented by document analysis. Data were analyzed using the interactive model of data condensation, data display, and conclusion drawing and verification, while the credibility of the findings was ensured through source and technique triangulation. The findings reveal that the implementation of the two-way symmetrical communication model is reflected in three main communication practices: disseminating information to students' parents, conducting persuasive communication with community members through both direct and indirect approaches, and systematically accommodating and responding to public opinions to improve institutional policies. These communication practices foster mutual understanding, trust, and collaborative relationships between the madrasah and the community while facilitating mutually beneficial solutions to emerging issues. This study contributes to the literature by demonstrating how the two-way symmetrical communication model can be effectively adapted within Islamic educational institutions to strengthen community engagement and institutional sustainability.